A study on personal selling element as a factors contribute to successful wealth planner in Prudential Assurance Malaysia Berhad Melaka / Muhammad Rofikhi Malik Ridzwan - Malik Ridzwan, Muhammad Rofikhi (Faculty of Business and Management, 2009)
This research was conducted for the purposed of finding the “Factors Contribute to Successful Wealth Planner in Prudential Assurance Berhad, Melaka”. The main objective of this research was to determine the various factors to become successful wealth planner. Those factors are active listening, adaptive selling, handling objection, closing skills, negotiating skills and prospecting skills. The respondent of this study would be the wealth planner in the Prudential Assurance Berhad in Melaka only. 50 questionnaires will be distributed and the conclusion of this study was the outcome from the survey analysis and findings.